2017
DOI: 10.1177/1758573216687273
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of hydrodilatation as part of a combined service for stiff shoulder

Abstract: (2017) 'Analysis of hydrodilatation as part of a combined service for sti shoulder.', Shoulder and elbow., 9 (3). pp. 169-177. Further information on publisher's website:https://doi.org/10.1177/1758573216687273Publisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
0
14
0
4
Order By: Relevance
“…However, the available evidence on the effects of hydrodilatation is inconclusive. 25,120,121 A meta-analysis 120 of seven small RCTs concluded that hydrodilatation combined with corticosteroid has no significant clinical effect on pain, disability and shoulder movements compared with corticosteroid alone. A further RCTs 25 in 50 participants with severe frozen shoulder found ACR compared with hydrodilatation improved OSS at 6 months.…”
Section: Hydrodilatation As One Of the Uk Frost Treatmentsmentioning
confidence: 99%
“…However, the available evidence on the effects of hydrodilatation is inconclusive. 25,120,121 A meta-analysis 120 of seven small RCTs concluded that hydrodilatation combined with corticosteroid has no significant clinical effect on pain, disability and shoulder movements compared with corticosteroid alone. A further RCTs 25 in 50 participants with severe frozen shoulder found ACR compared with hydrodilatation improved OSS at 6 months.…”
Section: Hydrodilatation As One Of the Uk Frost Treatmentsmentioning
confidence: 99%
“…Further, the patients with FS should also be treated for underlying medical disorder (DM and thyroid dysfunction) as poor control of these disorders may result in prolonged severity of disease. Although diabetics often tend to have severe disease and require prolonged conservative treatment and require surgical treatment more often than non-diabetics [42][43][44], one must not give up conservative treatment trial and expedite surgical treatment in diabetics.…”
Section: Treatmentmentioning
confidence: 99%
“… 13 Adipocytes also secrete IL-13, which has been shown to cause liver fibrosis in mouse models, and most likely also contributes towards synovial and connective tissue fibrosis. 18 Furthermore, adipocytes produce and secrete free fatty acids, which result in the up-regulation of pro-inflammatory mediators and exacerbated production of inflammatory cytokines. 14 , 19 , 20 Free fatty acids also promote neutrophil survival and decrease apoptotic cell removal by macrophages and other phagocytic cells, exacerbating collagen deposition in the glenohumeral capsule, among other extracellular matrix components, resulting in a rigid and painful shoulder.…”
Section: Etiopathophysiology Of Collagen Musculoskeletal Disordersmentioning
confidence: 99%